Fast synaptic excitatory neurotransmission in the human submucosal plexus. Issue 8 (7th May 2021) - Michel, Klaus; Krüger, Dagmar; Schäuffele, Stefanie; Zeller, Florian; Demir, Ihsan Ekin; Theisen, Jörg; Schemann, Michael
Abstract: Background: Acetylcholine is the main excitatory neurotransmitter in the enteric nervous system (ENS) in all animal models examined so far. However, data for the human ENS is scarce. Methods: We used neuroimaging using voltage and calcium dyes, Ussing chamber, and immunohistochemistry to study fast synaptic neurotransmission in submucosal plexus neurons of the human gut. Key Results: Electrical stimulation of intraganglionic fiber tracts led to fast excitatory postsynaptic potentials (fEPSPs) in 29 submucosal neurons which were all blocked by the nicotinic antagonist hexamethonium. The nicotinic agonist DMPP mimicked the effects of electrical stimulation and had excitatory effects on 56 of 73 neurons. The unselective NMDA antagonist MK‐801 blocked fEPSPs in 14 out of 22 neurons as well as nicotine evoked spike discharge. In contrast, the application of NMDA showed only weak effects on excitability or calcium transients. This agreed with the finding that the specific NMDA antagonist D‐APV reduced fEPSPs in only 1 out of 40 neurons. Application of AMPA or kainite had no effect in 41 neurons or evoked spike discharge in only one out of 41 neurons, respectively. Immunohistochemistry showed that 98.7 ± 2.4% of all submucosal neurons ( n  = 6 preparations, 1003 neurons) stained positive for the nicotinic receptor (α1, α2 or α3 –subunit). Hexamethonium (200 µM) reduced nerve‐evoked chloride secretion by 34.3 ± 18.6% ( n  = 14 patients), whereas D‐APV had no effect. Conclusion & Inference: Acetylcholine is the most important mediator of fast excitatory postsynaptic transmission in human submucous plexus neurons whereas glutamatergic fEPSPs were rarely encountered. Abstract : All neurons in the human submucous plexus receive fEPSPs. All fEPSPs have a cholinergic, nicotinic component. Only very few fEPSPs show a purinergic component. Even less have a glutamatergic component.